HIV-1 Infection of T Lymphocytes and Macrophages Affects Their Migration via Nef - Vérollet, Christel; Le Cabec, Véronique; Maridonneau-Parini, Isabelle (Frontiers in Immunology, 2015)
The human immunodeficiency virus (HIV-1) disseminates in the body and is found in several organs and tissues. While HIV-1 mainly targets both CD4+ T lymphocytes and macrophages, it has contrasting effects between these cell populations. HIV-1 infection namely reduces the viability of CD4+ T cells, whereas infected macrophages are long-lived. In addition, the migration of T cells is reduced by the infection, while HIV-1 differentially modulates the migration modes of macrophages. In 2-dimensions (2D) assays, infected macrophages are less motile compared to the control counterparts. In 3D environments, macrophages use two migration modes that are dependent on the matrix architecture: amoeboid and mesenchymal migration. HIV-1 infected macrophages exhibit a reduced amoeboid migration but an enhanced mesenchymal migration, via the viral protein Nef. Indeed, the mesenchymal migration involves podosomes, and Nef stabilizes these cell structures through the activation of the tyrosine kinase Hck, which in turn phosphorylates the Wiskott Aldrich Syndrome Protein (WASP). WASP is a key player in actin remodeling and cell migration. The reprogramed motility of infected macrophages observed in vitro correlates in vivo with enhanced macrophage infiltration in experimental tumors in Nef-transgenic mice compared to control mice. In conclusion, HIV infection of host target cells modifies their migration capacity; we infer that HIV-1 enhances virus spreading in confined environments by reducing T cells migration, and facilitates virus dissemination into different organs and tissues of the human body by enhancing macrophage mesenchymal migration.